2013
DOI: 10.1590/s1415-43662013000900003
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis and yield of tomato crop under different irrigation depths

Abstract: The influence of irrigation depth was evaluated on tomato crop hybrid Debora plus for salad in a field experiment in split-block design with five treatments (irrigation depth of 40, 60, 80, 100 and 120% of crop evapotranspiration -ETc) and four replications. During the experiment, ten plant samples were collected to determine phytomass and leaf area to estimate plant growth parameters for different depths of irrigation. Results showed maximal growth between 70 and 80 days after transplanting in all treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
6
15
0
7
Order By: Relevance
“…Tendência semelhante sob a redução da massa média dos frutos foi observado por Koetz et al (2010); Silva et al (2013) ao testarem diferentes lâminas de irrigação na cultura do tomate. Trabalhos que revelam efeito negativo do déficit hídrico sob o peso dos frutos foram evidenciados por Madrid et al (2009) Alvarenga (2004) ressalta-se que a ocorrência de temperatura elevada do local na época de floração, aumenta o número de abortamento das flores resultando em queda de produtividade.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Tendência semelhante sob a redução da massa média dos frutos foi observado por Koetz et al (2010); Silva et al (2013) ao testarem diferentes lâminas de irrigação na cultura do tomate. Trabalhos que revelam efeito negativo do déficit hídrico sob o peso dos frutos foram evidenciados por Madrid et al (2009) Alvarenga (2004) ressalta-se que a ocorrência de temperatura elevada do local na época de floração, aumenta o número de abortamento das flores resultando em queda de produtividade.…”
Section: Resultsunclassified
“…Esses resultados foram inferiores aos 60,5 t ha -1 encontrados por Monte et al (2013) testando a mesma percentagem de reposição de água (120 % ETo). Essa diferença na produção pode ser atribuída à diferença do híbrido utilizado, a textura do solo e o clima.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Resultado contrário foi obtido por Monte et al (2013), que encontraram aumento na produção de frutos não comerciais (defeituosos) nas lâminas de 100 e 120% da ETc. (FAO, 2012).…”
Section: Resultsunclassified
“…Moreover, according to Monte et al (2013), tomato is sensitive to high temperatures, and plants subjected to temperatures above the ideal range reduce photosynthesis and increase mitochondrial respiration, which may decrease their carbon biomass (PIMENTEL, 1998). Santana et al (2010) evaluated tomato crops under prolonged and severe water deficit and reported a reduced fruit growth.…”
Section: Revmentioning
confidence: 99%